The Susceptibility of Klebsiella Pneumoniae Strains Isolated from COVID-19 Patients to Commercially Available Bacteriophage Medications - B. I. Aslanov; A. E. Goncharov; S. D. Konev; A. S. Mochov; D. A. Azarov; E. А. Lebedeva; A. V. Kuleshova; V. V. Kolodzhieva; E. N. Kolosovskaya; A. M. Nifontova; D, A. Lioznov (Антибиотики и Химиотерапия)
Background. Superinfection caused by Klebsiella pneumoniae occupies a leading position in the structure of bacterial complications in COVID-19 patients. The intensive circulation of Klebsiella in specialised hospitals has contributed to the consolidation of the most clinically and epidemiologically important strains of this pathogen, in particular, representatives of hypervirulent and carbapenem-resistant clonal lines, which have not lost their relevance even in the post-pandemic period. The use of bacteriophages as therapeutic and anti-epidemic agents seems justified given the widespread use of multidrugresistant strains of K. pneumoniae.Aim of the study. To evaluate the susceptibility of K. pneumoniae strains associated with nosocomial infections in patients with COVID-19 to polyvalent bacteriophage medications.Materials and methods. The study included 96 non-repeating K. pneumoniae strains isolated from clinical material of patients admitted to a major hospital in St. Petersburg with severe and moderate forms of COVID-19 from May 2020 to January 2021. The susceptibility of clinical strains to bacteriophages was assessed using the spot test analysis. Commercially available bacteriophage preparations used for testing included the following: purified polyvalent pyobacteriophage, sextaphage, and purified polyvalent Klebsiella pyobacteriophage. In order to identify the probable mechanisms of resistance of hospital strains of K. pneumoniae, the nucleotide sequences of the genomes of 6 strains of this pathogen belonging to the dominant hospital genetic lines ST3, ST39, ST307, ST395, ST874 were studied.Results. Negative results of spot tests were observed in 32.29% (95% CI=23.8–42.2) of cases; in general, the proportion of patients eligible for treatment with phage therapy was 49% (95% CI=39.2–58.8). Loci of class 1 subtypes IV-A3 and I-E, potentially associated with resistance to CRISPR-Cas, were identified in the genome structure of the studied strains, as well as a number of prophage sequences potentially associated with resistance to bacteriophages.Conclusion. The study demonstrated low activity of polyvalent bacteriophage medications against K. pneumoniae strains causing nosocomial infections in patients with COVID-19. Increasing the diversity of bacteriophage strains active against epidemiologically relevant K. pneumoniae clones can expand the possibilities of phage therapy for Klebsiella infections. The rational use of medications containing these bacteriophages is possible within the paradigm of personalised phage therapy.